Development of Composition and Technologies of Dental Film with Ketorolac Trometamine - Bakhrushina, Elena O.; Demina, Natalia B.; Kashperko, Alena S.; Vakina, Marina G.; Anurova, Maria N.; Zhilyakova, Elena T.; Krasnyuk, Ivan I. (Drug Research, 2020)
The report presents the results of the development of dental films with ketorolac trometamine based on the natural biodegradable polymers from the groups of sodium alginates and xanthan gums in combination with lightly crosslinked acrylic polymer carbopol. Physicochemical properties, such as moisture, mucoadhesion, thickness, tensile strength, disintegration in phosphate buffer were determined in obtained samples of this dosage form. A comparison of physicochemical properties of experimental samples and commercial model of dental film has allowed establishing the perspective composition of complex matrix of films with ketorolac trometamine for use in dentistry.
Keywords: anti-inflammatory drugs; pharmaceutics; drug research; drug delivery